A Further Note on Dynamic Economics - Johnson, Harry G. (Review of Economic Studies, 1955)
Journal Article A Further Note on Dynamic Economics Get access Harry G. Johnson Harry G. Johnson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 3, 1955, Pages 245–246, https://doi.org/10.2307/2295731 Published: 01 December 1955